The influence of service quality on customer satisfaction at Kopi Sadis Medan cafe - Marwati, Devi; Sari, Dian Purnama (Jurnal Ekonomi, 2024)
The purpose of this study is to find out whether service quality affects customer satisfaction at Kopi Sadis Café Medan. The sample of this study was 106 people. Data analysis with Simple Regression test with model specification (classic hypothesis test), hypothesis testing with coefficient determination test (R2) gave an R value of 0.422, which means that there is a fairly close relationship between service quality and customer satisfaction. Kopi Sadis Café Medan or 42.2% and the test part (t-test), while SPSS is used to process the data. The research results show that service quality can explain the existence of the customer satisfaction variable, except that service quality partially and significantly affects customer satisfaction.